ATCFS : effective connectivity restoration scheme for underwater acoustic sensor networks - Liu, Lingfeng (2019)
Underwater acoustic sensor network (UASN) has become one of the enabling technologies for the development of future ocean observation systems (OOSs). However, the UASN could be severely damaged because of the harsh environment that causes the simultaneous failure of many sensor nodes, thus leading to the partition of the network into multiple disconnected segments. In this paper, we studied the crucial issue to reestablish the network connectivity with the least quantity of employed relay nodes. To achieve a clear understanding of the issue, we present its integer nonlinear programming formulation, which is generally NP-hard. So, with the aim of solving the problem efficiently, an original heuristic scheme is proposed in this paper. Two fundamental algorithms are integrated into the scheme, namely, alternating tree construction and Fermat-point selection (ATCFS) as a whole. The results of extensive simulation experiment have confirmed that the ATCFS can solve this problem simply and effectively.